Proceso de interacción comunicacional entre jóvenes mestizos e indígenas en el ámbito universitario CASO: UTC. - Cruz Suárez, Elizabeth Rocío (2020)
The present research project called "Process of communicational interaction between young mestizos and indigenous people in the university environment, case of UTC", aims to analyze the communication process that young university students use with people who do not belong to the same cultural identity. There is a certain percentage of young people who belong to different cultural identities, which is why many of these people do not feel part of this society, which is why the communicational interaction they share is not always the same as the one they are used to receiving from the moment. in which they are born and formed as human beings. The ways of life that indigenous young people have from their birth differ from those of mestizos, which is why when they want to enter a university environment many of these young people change their way of speaking, dressing and even their way of thinking, and in this way to be able to fit in without discrimination on the part of the society of young mestizos. That is why in this project the approach that was given was Qualitative, because a focus group was carried out with mestizo and indigenous youth. There was the participation of young people from the Social Communication Career, in this space each of the participants shared their ideas, anecdotes, and ways of thinking about the communicational interaction they have with people who do not share their same cultural ideologies.